Rural Finance Policies 6 - Worldwide distribution and performance of microfinance institutions - Lapenu, Cecile (International Food Policy Research Institute, 2000)
How many microfinance institutions (MFIs) exist in the developing world? How well are they performing? What is their role in household economies? Are they using their funds efficiently? In 1999, the International Food Policy Research Institute (IFPRI) conducted a survey on MFIs in Asia, Africa, and Latin America to offer a new in-depth analysis of the distribution and performances of MFIs at the international level. This brief summarizes the results of the survey.